Analysis of microbial fuel cell for energy harvesting with waste water and molasses - ARUNGOVIND. M; PURUSHOTHAM. K.G; ARUNKUMAR. J; SENDILVELAN. S (International Journal of Pharma and Bio Sciences, 2017)
Sustainable energy production from organic waste is gaining research interest. Microbial fuel cell (MFC) is a technology in conversion of waste water to useful energy. In this work an attempt has been made to analyze the performance of waste water on microbial fuel cell. The living cells in the anode chamber utilize substrate for the growth maintenance; as a result the electrons are supplied. The goal of the present work is microbial fuel design and its characteristics based on electricity generated using MFC. Various waste waters are used as substrate in MFC which create changes in rate of power generation and adaption of bacterial strains in various waste causing in variation in electron transfer and power output.